“Women in an Alien Land”- Nuances of Diasporic Identity and Survival in Bharati Mukherjee’s Desirable Daughters - Parween, Shenaz (Integrated Journal for Research in Arts and Humanities, 2022)
Bharati Mukherjee, an Indian Born, Canadian/ American novelist has made a deep impression on the literary canvass. The prime premise of her works is the issues encountered by women in the foreign atmosphere. As a diasporic author most of her characters are ‘displaced’ and ‘alienated’ from the land of origin to USA where they are ‘simultaneously invisible’ as an individual and ‘overexposed’ as a racial minority. Focusing on Mukherjee’s Desirable Daughters, first of the trilogy including The Tree Bride and Miss New India, the present paper attempts to analyze the complexities of diasporic identity and the process of re-birth and re-invention of Indian women immigrants to adapt in the new world. A story of three sisters- Padma, Parvati and Tara, the novel showcases the problems of identity of Indian immigrant women in an alien society as they suffer from ‘no greater visibility but great marginality’. The problem with these sisters is not only that are immigrants but what makes their condition worse is their gender as well. Being with the label of ‘second sex’, these women are often confronted by a double quest- quest for identity as a woman first and second as a displaced human being in an alien world. The diasporic situation in fact entangles the sisters into a maze- standing between two worlds-with complex realities of unequal cultural dynamics of the traditional homeland and liberal spaces of host land- they tend to experience conflicting subjectivities of freedom and subjugation, yet they do find a way for self-exploration and deliberation to conceive new identities and move beyond the fixed definitions of diasporic Indian women. So, my paper will be a modest attempt to unravel the nuances of diasporic identity which is always a matter of ‘becoming’ as well as of ‘being’ and to highlight the extremely individualistic ways of survival of the three immigrant sisters in an apparently alien culture.